Design of LTCC microstrip patch antenna at 28 GHz / Anwar Ariff Mohd Yusof - Mohd Yusof, Anwar Ariff (2013)
This paper presents a microstrip patch antenna design that is suitable for satellite uplink communication. It consists of multilayer substrate that will make the coverage more efficient while operates at 28 GHz which is for Ka-Band. The specification for the proposed patch antenna is it has a frequency of 28 GHz, Ferro A6-S LTCC substrate with permittivity 5.9, a substrate thickness of 0.096 mm and copper thickness of 0.01 mm. The designed parameters for the proposed antenna were calculated using transmission line model equation. The simulation process was done using the circuit Computer Simulation Technology (CST) Microwave Studio software. The characters of antenna such as return loss, bandwidth, gain, directivity and voltage standing wave ratio (VSWR) have been investigated in the simulation. The antenna has eight layers of substrate where the simulation computed at 28 GHz frequency, antenna return loss of-46.99 dB, VSWR value of 1.009 and 3.13% bandwidth. The patch antenna is added with EBG and parasitic patch to investigate the changes in the results. It is proven that the antenna with the combination of EBG and parasitic patch have wider bandwidth.